Evidence for a humid interval at ∼56–44 ka in the Levant and its potential link to modern humans dispersal out of Africa. Issue 124 (November 2018) - Langgut, Dafna; Almogi-Labin, Ahuva; Bar-Matthews, Miryam; Pickarski, Nadine; Weinstein-Evron, Mina
Abstract: This study provides a detailed reconstruction of the paleoenvironmental conditions that prevailed during one of the periods of modern human migration out of Africa and their occupation of the Eastern Mediterranean-Levant during the Late Middle Paleolithic-Early Upper Paleolithic. Tracing the past vegetation and climate within the Eastern Mediterranean-Levant region is largely based on a south-eastern Mediterranean marine pollen record covering the last 90 kyr (core MD-9509). The various palynomorphs were linked to distinct vegetation zones that were correlated to the two climate systems affecting the study area: the low-latitude monsoon system and the North Atlantic-Mediterranean climate system. The bioprovince palynological markers show that during the period between ∼56 and 44 ka, which covers the early part of Marine Isotope Stage 3 (MIS 3), there was an increase in transportation of pollen from Nilotic origin and a rise in dinoflagellate cyst ratios. These changes coincided with maximum insolation values at 65°N, which led to an enhancement in Nile River discharge into the Eastern Mediterranean following the intensification of the African monsoonal system. At the same time, the rise in Mediterranean arboreal pollen values (broadleaved, coniferous and deciduous temperate trees) is most likely driven by increased precipitation related to the intensification of the North Atlantic-Mediterranean climate system. The ∼56–44 ka wet event coincides with Dansgaard-Oeschger interstadials 14 and 12 and with a warming phase in the Levant, as evidenced by the melting of permafrost along the higher elevations of Mount Hermon. We suggest that African modern humans were able to cross the harsher arid areas due to the intensification of the monsoonal system during the first part of MIS 3, and inhabit the Eastern Mediterranean-Levant region where climatic conditions were favorable (wetter and warmer), even in the currently semiarid/steppe regions.